Beta Cell Function as a Baseline Predictor of Weight Loss After Bariatric Surgery - Borges-Canha, Marta; Neves, João Sérgio; Mendonça, Fernando; Silva, Maria Manuel; Costa, Cláudia; M. Cabral, Pedro; Guerreiro, Vanessa; Lourenço, Rita; Meira, Patrícia; Salazar, Daniela; Ferreira, Maria João; Pedro, Jorge; et al. (Frontiers in Endocrinology, 2021)
Background: Obesity is a multifactorial disease which is strongly associated to other metabolic disorders. Bariatric surgery is the most effective treatment of morbid obesity. The role of beta cell function in weight loss after bariatric surgery is uncertain. Aim: To evaluate the association between beta cell function and percentage of total body weight loss (TBWL%) one, two, three and four years after bariatric surgery in patients with morbid obesity. Methods: Retrospective longitudinal study in patients with morbid obesity followed in our center between January 2010 and July 2018. Patients were excluded if they had diabetes at baseline or missing data on the needed parameters. We evaluated baseline Homeostatic Model Assessment of IR, Homeostatic Model Assessment of β-cell function (HOMA-beta), Quantitative Insulin Sensitivity Check Index and Matsuda and DeFronzo index, and TBWL% at years one to four. Linear regression models were used to evaluate the association of indexes of insulin resistance with TBWL% (unadjusted and adjusted for age, sex, BMI and type of surgery). Results: 1561 patients were included in this analysis. HOMA-beta was negatively associated with TBWL% at second-, third- and fourth-years post-surgery (β=-1.04 [-1.82 to -0.26], p<0.01; β=-1.16 [-2.13 to -0.19], p=0.02; β=-1.29 [-2.64 to 0.06], p=0.061, respectively). This was not observed in the first-year post-surgery nor for the other indexes. Glycaemia at baseline was positively associated to EWL% at second- and third-years post-surgery. Conclusion: β-cell function at baseline seems to be associated to long term weight loss, explicitly after the first year post bariatric surgery. This might be a helpful predictor of weight loss in clinical practice.